Alternative splicing: an important mechanism for myometrial gene regulation that can be manipulated to target specific genes associated with preterm labour - Tyson-Capper Alison (BMC, 2007)
Abstract Considerable effort has been expended in attempting to distinguish genes that contribute to initiating the onset of term and preterm labour (PTL) from those that change in expression as a consequence of the progression of labour. The ability to define more clearly the genes involved in triggering labour contractions should lead to the development of new effective and safer strategies to prevent preterm birth. There is ample evidence to suggest that specific genes are co-ordinately regulated within the upper and lower regions of the myometrium prior to and during parturition and many of these genes are regulated by alternative pre-mRNA splicing. This mini-review highlights that expression of a range of different splicing factors, with defined roles in pre-mRNA splicing, is both temporally and spatially regulated within the uterine smooth muscle during pregnancy and labour. Moreover, several of these splicing factors play key roles in controlling the differential expression of specific regulatory proteins involved in uterine signalling and uterine quiescence. In addition, antisense morpholino oligonucleotide manipulation of pre-mRNA splicing may have potential in defining and targeting uterine pro-labour genes and thus contribute to the development of new therapeutic approaches to prevent PTL.